Birth Preparedness and Complication Readiness among Pregnant and Recently Delivered Women in Gandhinagar District, Gujarat, India: A Community-based Cross-sectional Study - Yagnik, Hardik; Patel, Punit; Ninama, Neha; Rahul, Kirtikumar (Indian Journal of Community Health, 2023)
Background: Birth Preparedness and Complication Readiness (BPCR) helps in improving the effective utilization of available maternal and newborn health care services through knowledge of danger sign, identifying birth place and attendant, means of transportation, managing fund for an emergency, birth companion and identification of blood donor. Aim: To find the association between socio-demographic characteristics and BPCR index indicators. Settings and Design: A cross-sectional study was conducted among the recently delivered and pregnant women in urban and rural areas of the Gandhinagar district of Gujarat. Methods and Material: Total 420 pregnant and recently delivered women from urban and rural areas were interviewed for study. A pretested semi-structured questionnaire was used to interview women at household setting. BPCR index is estimated by set of 7 quantifiable indicators and expressed in the percentage of women with specific characteristics. Results: Regarding ANC registration within 12th weeks of pregnancy and skilled birth attendant for delivery. Significant difference was observed with variable like APL/BPL status, education of women and their husband, parity and type of family. Conclusions: Hindu religion, APL economic status, higher education level, joint family, high parity and joint family were found important predictor of better BPCR practice.